Antithrombotic Treatment in Neonatal Cerebral Sinovenous Thrombosis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2010)
Researchers involved with the International Pediatric Stroke Study enrolled 341 neonates with cerebral sinovenous thrombosis (CSVT) from 10 countries from 2003 through 2007.